2000
DOI: 10.1002/1097-0215(20000915)87:6<812::aid-ijc9>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Germline alterations in the cyclooxygenase-2 gene are not associated with the development of extracolonic manifestations in a large Swiss familial adenomatous polyposis kindred

Abstract: Familial adenomatous polyposis (FAP) is an autosomal dominant condition leading to the development of multiple colorectal polyps and other features. Intrafamilial variation in phenotype is known to occur in FAP; despite carrying the same causing mutation in the APC gene, disease expression may considerably differ in affected individuals, likely due to the existence of modifier genes. Several lines of evidence suggest the cyclooxygenase‐2 (COX‐2) gene to be a candidate modifier in FAP. Since COX‐2 appears to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…40 The presence of other naturally occurring polymorphisms in the promoter of COX-2 has been reported; however, none have so far been shown to be functional or to be associated with inflammatory disease. 18,19 None of these changes are located within recognized transcription factor binding sites. We did not identify these changes in the present study; however, this may be due to low allele frequencies and the ethnic group studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…40 The presence of other naturally occurring polymorphisms in the promoter of COX-2 has been reported; however, none have so far been shown to be functional or to be associated with inflammatory disease. 18,19 None of these changes are located within recognized transcription factor binding sites. We did not identify these changes in the present study; however, this may be due to low allele frequencies and the ethnic group studied.…”
Section: Discussionmentioning
confidence: 99%
“…We did not identify these changes in the present study; however, this may be due to low allele frequencies and the ethnic group studied. 18,19 The effect of Ϫ765GϾC and other COX-2 gene variants may have implications in the use of NSAIDs. Regular use of NSAIDs has proven effective in reducing the risk of developing diseases, in particular, cardiovascular disease and bowel cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several SNPs in COX-2 have been reported previously, but many of these polymorphisms seem to be functionally insignificant and not associated with susceptibility to cancer. [20][21][22] However, it has been shown that the À765G4C COX-2 polymorphism has been reported to disrupt an Sp1-binding site and displays a lower promoter activity, 14 and interestingly, a higher COX-2 expression has been found in the normal mucosa of patients with FAP who carried the À765GG polymorphism, 15 than carriers of the C allele. These findings awaken curiosity within the field of gastric cancer, as to whether it may also play a role here.…”
Section: Discussionmentioning
confidence: 99%
“…However, a limited number of polymorphisms in the COX-2 promoter region, with potential impact on the COX-2 phenotype, have been identified. 15,16 Unfortunately, these polymorphisms were not located in any known transcription factor binding site that could potentially impact transcription, did not result in an inactive COX-2 enzyme, or change the NSAID susceptibility and the metabolite profile. Altered function of COX-2 had been hypothesized to change the number of colonic polyps in patients with an inherited predisposition to colon cancer, and two COX-2 gene sequencing studies in patients with adenomatous polyposis coli (APC) have been reported.…”
Section: See P 1631mentioning
confidence: 99%